2018
DOI: 10.1111/1346-8138.14221
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of psoriasis following scabies infection: A nationwide population‐based matched‐cohort study

Abstract: Both scabies and psoriasis are pruritic inflammatory skin diseases. The clinical manifestations are similar and provocation of psoriasis by mite bite was reported. The association between scabies and psoriasis was not investigated before. We conducted this nationwide population-based matched-cohort study to describe if patients with a diagnosis of scabies have a different risk of developing new psoriasis. From the National Health Insurance Research Database of Taiwan, patients with scabies (n = 5137) were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
6
0
1
Order By: Relevance
“…If blistering is present, then bullous pemphigoid [45, 46] and dermatitis herpetiformis should be considered. Additionally, there appears to be an increased risk of developing psoriasis following scabies [47]. In infants and young children, the differential diagnosis might include Langerhans cell histiocytosis [48, 49], papular urticaria and infantile acropustulosis, and in tropical settings pyoderma without scabies is an important consideration.…”
Section: Treatmentmentioning
confidence: 99%
“…If blistering is present, then bullous pemphigoid [45, 46] and dermatitis herpetiformis should be considered. Additionally, there appears to be an increased risk of developing psoriasis following scabies [47]. In infants and young children, the differential diagnosis might include Langerhans cell histiocytosis [48, 49], papular urticaria and infantile acropustulosis, and in tropical settings pyoderma without scabies is an important consideration.…”
Section: Treatmentmentioning
confidence: 99%
“…In 1986, Keipert (131) reported that an individual with crusted scabies developed psoriasis. Liu et al (132) performed a nationwide study and demonstrated a potential association between scabies and psoriasis. Patients with scabies were reported to have an increased risk of psoriasis (hazard ratio, 3.03).…”
Section: Other Microorganismsmentioning
confidence: 99%
“…There is a possible association between scabies and increased risk of developing psoriasis. Psoriasis should be taken under consideration in differential diagnosis of treatment-resistant scabies (20).…”
Section: Julia Nowowiejska Monika Emilia Król I Innimentioning
confidence: 99%
“…a zwiększonym ryzykiem zachorowania na łuszczycę. Łuszczycę należy brać pod uwagę w diagnostyce różnicowej przy występowaniu świerzbu opornego na leczenie (20). Nawrót świerzbu wykazano w 14% dokumentacji pacjentów.…”
Section: Scabies Is An Infectious and Contagious Diseaseunclassified